2009
DOI: 10.1186/1471-2288-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of NNTs in RCTs with time-to-event outcomes: A literature review

Abstract: BackgroundThe number needed to treat (NNT) is a well-known effect measure for reporting the results of clinical trials. In the case of time-to-event outcomes, the calculation of NNTs is more difficult than in the case of binary data. The frequency of using NNTs to report results of randomised controlled trials (RCT) investigating time-to-event outcomes and the adequacy of the applied calculation methods are unknown.MethodsWe searched in PubMed for RCTs with parallel group design and individual randomisation, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 24 publications
1
29
1
1
Order By: Relevance
“…36,37 The difference in NNT between treatment groups was tested using a z-test; P ≤ .05 was considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The difference in NNT between treatment groups was tested using a z-test; P ≤ .05 was considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis of time-to-event outcomes the use of survival time methods is required. However, a recent systematic literature review of RCTs with parallel group design and individual randomization published in 4 major medical journals in the period [2003][2004][2005] found that in the case of time-to-event outcomes inadequate methods to estimate NNTs have been used in 50% of articles presenting NNTs (17 of 34 articles) [10]. In studies in which the effects of covariates are taken into account to estimate relative effect measures such as adjusted odds ratios, these covariates should also be used to estimate adjusted NNTs [13].…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…Additionally, the explanatory document of the Consolidated Standards of Reporting Trials (CONSORT) statement [9] exposes that NNTs are helpful for expressing the results of studies with binary and survival time outcomes. In spite of its widespread use, NNTs are frequently misused, incorrectly calculated, incompletely or misleadingly presented, and incorrectly interpreted [2,10,11]. There are various reasons for misleading applications of NNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac events were reduced from 10.8 events/ 100 patient years to 7.8 events per 100 patient years, (HR 0.68; 95% CI 0.51-0.90) for a number needed to treat (NNT) of 33 patients for one year to prevent one cardiac event. 10 Treatment effects adjusted for Beta-blockers, angiotensin converting enzyme/angiotensin receptor blockers or sevelamer usages, serum calcium and phosphate levels were all well matched and no signifi cant interactions with mortality or primary composite endpoints were found. Traditional cardiac risk factors such as LDL-cholesterol, blood pressure (BP) and smoking were not associated with signifi cant cardiac outcomes.…”
Section: Cardiac Event Reduction Inmentioning
confidence: 90%